The deformation of marine snow enables its disaggregation in simulated oceanic shear - Song, Yixuan; Burd, Adrian B.; Rau, Matthew J. (Frontiers in Marine Science, 2023)
Understanding the effect of hydrodynamics on aggregate size and structure is key to predicting mass transport in the aquatic environment. Aggregation theory of particles is well established but our knowledge of deformation processes, biological bonding forces, and their effects on fragmentation of aquatic aggregates is still limited. To better comprehend fragmentation processes and adhesion forces we implemented breakup experiments with diatom and microplastic aggregates made in the laboratory. We captured a substantial number of events showing deformation and subsequent fragmentation of these aggregates in an oscillatory shear flow. Polystyrene and polyethylene aggregates showed distinct fragmentation strengths and provided comparative upper and lower limits to the biological bonding strength of the diatom aggregates. Additionally, we employed a force balance model to evaluate attractive interactions within clusters of particles using the Lagrangian stress history and morphology. We found that the fractal structures of aggregates led to a power law of breakup strength with size and that time-integrated stress governed the overall fragmentation process. We also found that the weakening of the aggregates through deformation with shear exposure enabled their disaggregation at very low shear rates typical of the ocean environment.